A rattle: On the other frontier, and Chabani Manganyi’s “Making strange” - Truscott, Ross (PINS-Psychology in Society, 2018)
This paper reflects on Chabani Manganyi’s “Making strange: Race science and ethnopsychiatric discourse” on the occasion of its republication in PINS. “Making strange” is placed in relation to the critique of what Marxist revisionist historian, Martin Legassick called the liberal frontier tradition of South African historiography, a tradition that posited the eighteenth century frontier of the Cape colony as the origin of South African race prejudice. Thinking about the implications of this critique for critical psychology, specifically for psychoanalytically inclined scholarship, the paper pursues what Manganyi calls “another beginning” of what he names as a “chain of discourse which is sometimes described as colonial discourse”. The paper poses the basic question of what constitutes the links in this “chain”.